Cholate-based nano emulgel of 1,1-dimethylbiguanide can diminish the liver damage in NAFLD induced by high-fat diet - Heba F. Salem, Mohammed M. Nafady, Adel A. Ali, Nermeen M. Khalil, Amani A. Elsisi (Journal of Applied Pharmaceutical Science, 2023)
NAFLD (nonalcoholic fatty liver disease) is a widely spread disease that, till now, has no approved therapy, and enhancing the patient’s case depends only on lifestyle modification. In this research, cholate-based 1,1-dimethylbiguanide (metformin HCl) was incorporated into an emulgel to investigate its transdermal effect in treating NAFLD. metformin HCl cholate-based nanovesicles were prepared with the solvent vaporization technique. Vesicles are imaged by transmission electron microscope to ensure the vesicles formation, and their charge is detected to inspect their stability. The vesicles were then incorporated into a prepared Carbopol emulgel and then were characterized. Finally, an in vivo study on balb-c mice was performed to inspect its effect in treating NAFLD topically. The resulting vesicles were stable, sphere-shaped, and nonaggregated with a coarse surface. In addition, prepared emulgel was found clear and homogenous with general characteristics suitable for skin application. Furthermore, the rheology study showed a thixotropic performance. Finally, the in vivo study revealed an overall enhancement confirming the liver targeting ability of cholate-based bile salts. Cholate-based nanovesicles emulgel of metformin HCl is an approach for an acceptable level of evidence of effective transdermal treatment of NAFLD.